VD_FINDINFO AI 486/08 - 82/2010 vom 17. Februar 2010 - VD Tribunal cantonal (2010)
PRESTATION D'ASSURANCEAI, RECONSIDÉRATION, INEXACTITUDE MANIFESTE, CHOSE JUGÉE | 1 LAI, 4 LAI, 69 al. 1bis LAI, 16 LPGA, 53 al. 2 LPGA, 56 LPGA, 57 LPGA, 60 al. 1 LPGA, 61 let. g LPGA, 7 LPGA, 8 LPGA, 117 al. 1 LPA-VD, 2 LPA-VD, 49 LPA-VD, 55 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD